Geographic variation in prostate cancer survival in New South Wales. Issue 10 (2nd June 2014) - Yu, Xue Qin; Luo, Qingwei; Smith, David P; O'Connell, Dianne L; Baade, Peter D
Abstract: Objectives: To determine whether the previously reported urban–rural differential in prostate cancer survival remains after adjusting for demographic and clinical factors, and to investigate temporal trends in this differential. Design, setting and participants: Retrospective population‐based survival analysis of 68 686 men diagnosed with prostate cancer from January 1982 to December 2007 in New South Wales. Main outcome measures: Survival rate and relative excess risk (RER) of death over 10 years of follow‐up in relation to geographic remoteness after adjusting for other prognostic factors. Results: Overall, 10‐year survival increased during the study period, increasing from 57.5% in 1992–1996 and 75.7% in 1997–2001 to 83.7% in 2002–2007. The increasing trends were also observed across categories of geographic remoteness and socioeconomic status. Urban–rural differentials were significant ( P < 0.001) after adjusting for five important prognostic factors, with men living outside major cities having higher risk of death from prostate cancer (RER, 1.18 and 1.32 for inner regional and rural areas, respectively). Socioeconomic status was also a significant factor ( P < 0.001) for prostate cancer mortality, with the risk of dying being 34% to 40% higher for men living in socioeconomically disadvantaged areas than those living in least disadvantaged areas. There was no evidence that this inequality is reducing over time, particularly for men living in inner regional areas. Conclusions: Despite the increasing awareness of urban–rural differentials in cancer outcomes, little progress has been made. Appropriately detailed data, including details of tumour characteristics, treatment and comorbid conditions, to help understand why these inequalities exist are required urgently so interventions and policy changes can be guided by appropriate evidence.